Respuesta :

When you multiply a base with an exponent by a base with an exponent, you add the exponents together. (But you can only combine the exponents when the bases are the same)

For example:

[tex]x^3(x^1)=x^{(3+1)}=x^4[/tex]      (they have the same base of x)

[tex]y^3(x^2)=y^3x^2[/tex]     (you can't combine the exponents because they have different bases of y and x)

[tex]2^2(2^1)=2^{(2+1)}=2^3=8[/tex]

When you have a negative exponent, you move the base with the negative exponent to the other side of the fraction to make the exponent positive.

For example:

[tex]x^{-3}[/tex] or [tex]\frac{x^{-3}}{1} =\frac{1}{x^3}[/tex]

[tex]\frac{1}{y^{-2}} =\frac{y^2}{1}[/tex] or  [tex]y^{2}[/tex]

[tex]7^3*7^{-5}[/tex]      Add the exponents together

[tex]7^{(3+(-5))}[/tex]

[tex]7^{-2}[/tex]     Make the exponent positive

[tex]\frac{1}{7^2}[/tex]       Simplify

[tex]\frac{1}{49}[/tex]